Q-Starlike Functions of Order Alpha - Uçar, Faruk; Yılmaz, Bülent; POLATOĞLU, YAŞAR (TURKIC WORLD MATHEMATICAL SOC, 2018)
For all q is an element of (0, 1) and 0 <= alpha < 1 we define a class of analytic functions, so-called q-starlike functions of order alpha on the open unit disc D = {z : vertical bar z vertical bar < 1}. We will study this class of functions and explore some inclusion properties with the well-known class Starlike functions of order alpha.
Keywords: Q-starlike Functions; Distortion Theorem; Growth Theorem; Coefficient Inequality; Q-starlike İşlevleri; Bozulma Teoremi; Büyüme Teoremi; Katsayı Eşitsizliği